The Battle of Discourse of Regional Autonomy Issues in The Mass Media - KAWURYAN, MEGANDARU WIDHI (Jurnal Studi Pemerintahan, 2017)
This research started by knowing how mass media constructs the reality of re- gional autonomy issues. Studies on regional autonomy issue using communica- tion science perspective are still rare, while the role of mass media, according to Severin-Tankard (2007:15) is actually to form public opinions. Observers of con- structionism such as Shoemaker (1996) think that news broadcasted by mass media can make people have a certain point of view and construct a reality of an issue in the society, including regional autonomy issues. This study used framing text analysis.The model used was Robert N. Entman’s framing (1993)because in Entman’s concept, framing can be used to describe the selection process of an issue and emphasize certain aspects of a reality by the media. In this research, there are 3 media which were studied, i.e. Kompas newspaper, Jurnal Nasional newspaper, Kedaulatan Rakyat newspaper.The result of this study showed that at micro level there was frame difference in the reporting of Kompas, Jurnal Nasional and Kedaulatan Rakyat on Regional Autonomy Issues. Analysis at meso level showed that ownership and capital factors were still rather strong in influ- encing the frames of the studied media,macro levelthe battle of discourse of regional autonomy issues make the government finally changed the policy on regional autonomy.